Association between perceived social support and induced abortion: A study in maternal health centers in Lima, Peru - Sánchez-Siancas, Luis E. (2018)
Objectives This study aimed to assess the association between perceived social support and induced abortion among young women in Lima, Peru. In addition, prevalence and incidence of induced abortion was estimated. Methods/Principal findings A cross-sectional study enrolling women aged 18–25 years from maternal health centers in Southern Lima, Peru, was conducted. Induced abortion was defined as the difference between the total number of pregnancies ended in abortion and the number of spontaneous abortions; whereas perceived social support was assessed using the DUKE-UNC scale. Prevalence and incidence of induced abortion (per 100 person-years risk) was estimated, and the association of interest was evaluated using Poisson regression models with robust variance. A total of 298 women were enrolled, mean age 21.7 (± 2.2) years. Low levels of social support were found in 43.6% (95%CI 38.0%–49.3%), and 17.4% (95%CI: 13.1%–21.8%) women reported at least one induced abortion. The incidence of induced abortion was 2.37 (95%CI: 1.81–3.11) per 100 person-years risk. The multivariable model showed evidence of the association between low perceived social support and induced abortion (RR = 1.94; 95%CI: 1.14–3.30) after controlling for confounders. Conclusions There was evidence of an association between low perceived social support and induced abortion among women aged 18 to 25 years. Incidence of induced abortion was similar or even greater than rates of countries where abortion is legal. Strategies to increase social support and reduce induced abortion rates are needed.